(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The content of the Railway Statute of Primo de Rivera, which was approved by Royal Decree of 12 July 1924, is known at least by its more important features. However, its drawing up process hasn´t been studied with so much detail. In that process two different projects take place: the initial project, written by the lieutenantcolonel Gil Clemente, that caused alarm and opposition among the railway companies; and lieutenant Mayandía´s project, based on the former project, but with major changes, issued at the begining of 1924. This new project, which tempers the most discussed points of the former one regarding some of the criteria stated by therailway companies, will be debated in the recently created the Higher Council of Railways from the ending of February 1924 and will turn into the final Statue text. All things considered, the present work aims to study this very first phase of the Statute´s drawing up process, based on the data collected from different sourcesand, especially, in the Archive of the Spanish Railways Foundation. All of it is an introduction to the report´s analysis conducted by Flores de Lemus about the «Mayandía Project», granting the personal request of Primo de Rivera, a point consideredin a different paper.